Além das Caricaturas: Nazismo, Racismo e Ciências Raciais (1924-1936) | Beyond Caricatures: Nazism, Racism and Racial Sciences (1924-1936) - Henrique Varajidás (Political Observer, 2022)
This article brings forth, organizes and interprets a compound of historical-empirical evidence that allows questioning of two still standing pillars of Nazism political studies: the assumption that the racial aspect of nazi ideology enjoyed a relatively monolithic interpretation within the nazi movement; and the assumption that, after the conquest of power, the nazi Party-State conspired to unilaterally impose such “ideological dogma”, both in theory and practice, on German University and German society. Rather than confirm these oft-repeated conventions, we uncover a much more complex, dialectical and dynamic mesh of relationships involving ideology, pseudoscience and racial science within the nazi movement and under the nazi regime.